The athlete-scholarship program and the development of brazilian olympic sport (Impetus, 2021)
The Athletes' Exchange program is a public policy aimed at supporting national sports development. The program consists of monthly financial support for Brazilian athletes, it is divided into categories: basic, educational, national, international, Olympic and podium. The results achieved in the competitions of the sports modalities determine the level of support to be received. Athletes with physical limitations are also included in the program. The objective of this study is to carry out an analysis on the years 2005 - 2008 of operation of the program. For this, the official data provided by the virtual platform of the program were used. Among the results we find a growth of the program between the years 2005 to 2008, in addition, athletes from the southern and southeastern regions of the country were the most benefited. It can be concluded that the program has generated an improvement in the national sport, represented in the results achieved by the benefited athletes. Even so, the organization of the program must be reviewed, with a suggestion of a decentralization of its organization.